Atresia in the esophagus - Crisanto Abad Celuria; Abel Santana González-Chávez; Narciso Hernández Rodríguez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2005)
Esophageal atresia is the congenital lack of continuity of the esophagus with or without communication to the airway. Incidence is estimateed in 1 by 3000 to 4500 alive newborns. Cases in brothers are found and children of parents with atresia esophagus, nevertheless not a hereditary is recognized; also there is a greater frequency in twins. We presented the Good Clinical Practices Guideline for Esophageal atresia, approved by consensus in the 2nd National Good Clinical Practices Workshop in Pediatric Surgery (Manzanillo, Cuba, September 31 - October 3, 2002).